\(a>0\) và \(4a^2+a\sqrt{2}-\sqrt{2}=0\). Chứng minh:<...">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

NV
6 tháng 10 2021

\(a^2=\dfrac{\sqrt{2}}{4}\left(1-a\right)\)

\(\Rightarrow a^4=\dfrac{1}{8}\left(1-a\right)^2\)

\(\Rightarrow a^4+a+1=\dfrac{1}{8}\left(1-a\right)^2+a+1=\dfrac{1}{8}\left(a^2+6a+9\right)=\dfrac{1}{8}\left(a+3\right)^2\)

\(\Rightarrow\sqrt{a^4+a+1}-a^2=\sqrt{\dfrac{1}{8}\left(3+a\right)^2}-a^2=\dfrac{\sqrt{2}}{4}\left(a+3\right)-\dfrac{\sqrt{2}}{4}\left(1-a\right)=\dfrac{\sqrt{2}}{2}\left(a+1\right)\)

\(\Rightarrow\dfrac{a+1}{\sqrt{a^4+a+1}-a^2}=\dfrac{a+1}{\dfrac{\sqrt{2}}{2}\left(a+1\right)}=\sqrt{2}\)

6 tháng 10 2021

Dạ em cám ơn ạ

13 tháng 7 2017

2, a, \(a+\dfrac{1}{a}\ge2\)

\(\Leftrightarrow\dfrac{a^2+1}{a}\ge2\)

\(\Rightarrow a^2-2a+1\ge0\left(a>0\right)\)

\(\Leftrightarrow\left(a-1\right)^2\ge0\)( là đt đúng vs mọi a)

vậy...................

13 tháng 7 2017

Câu 1:

\(M=\sqrt{4+\sqrt{5\sqrt{3}+5\sqrt{48-10\sqrt{7+4\sqrt{3}}}}}\)

\(=\sqrt{4+\sqrt{5\sqrt{3}+5\sqrt{48-10\sqrt{\left(2+\sqrt{3}\right)^2}}}}\)

\(=\sqrt{4+\sqrt{5\sqrt{3}+5\sqrt{48-20-10\sqrt{3}}}}\)

\(=\sqrt{4+\sqrt{5\sqrt{3}+5\sqrt{\left(5-\sqrt{3}\right)^2}}}\)

\(=\sqrt{4+\sqrt{5\sqrt{3}+25-5\sqrt{3}}}\)

\(=\sqrt{4+5}=3\)

\(M=\sqrt{5-\sqrt{3-\sqrt{29-12\sqrt{5}}}}\)

\(=\sqrt{5-\sqrt{3-\sqrt{\left(2\sqrt{5}-3\right)^2}}}\)

\(=\sqrt{5-\sqrt{3-2\sqrt{5}+3}}\)

\(=\sqrt{5-\sqrt{\left(\sqrt{5}-1\right)^2}}\)

\(=\sqrt{5-\sqrt{5}+1}=\sqrt{6-\sqrt{5}}\)

7 tháng 10 2018

b) \(\dfrac{\sqrt{a}}{\sqrt{a}-\sqrt{b}}-\dfrac{\sqrt{b}}{\sqrt{a}+\sqrt{b}}-\dfrac{2b}{a-b}\)

\(=\dfrac{\sqrt{a}}{\sqrt{a}-\sqrt{b}}-\dfrac{\sqrt{b}}{\sqrt{a}+\sqrt{b}}-\dfrac{2b}{\left(\sqrt{a}-\sqrt{b}\right)\left(\sqrt{a}+\sqrt{b}\right)}\)

\(=\dfrac{\sqrt{a}\left(\sqrt{a}+\sqrt{b}\right)-\sqrt{b}\left(\sqrt{a}-\sqrt{b}\right)-2b}{\left(\sqrt{a}-\sqrt{b}\right)\left(\sqrt{a}+\sqrt{b}\right)}\)

\(=\dfrac{a+\sqrt{ab}-\sqrt{ab}+b-\sqrt{ab}+b-2b}{a-b}\)

\(=\dfrac{a}{a-b}\)

7 tháng 10 2018

khúc \(\dfrac{a}{a-b}\) sai nhé

\(=\dfrac{a-b}{a-b}=1\)

2 tháng 10 2018

ko biet

a: \(=2ab\cdot\dfrac{-15}{b^2a}=\dfrac{-30}{b}\)

b: \(=\dfrac{2}{3}\cdot\left(1-a\right)=\dfrac{2}{3}-\dfrac{2}{3}a\)

c: \(=\dfrac{\left|3a-1\right|}{\left|b\right|}=\dfrac{3a-1}{b}\)

d: \(=\left(a-2\right)\cdot\dfrac{a}{-\left(a-2\right)}=-a\)